New evidence regarding the effects of contract farming on agricultural labor use - Anette Ruml; Matin Qaim (Agricultural Economics, 2021)
Contractual agreements between smallholder farmers and agribusiness companies have gained in importance in many developing countries. While productivity and income effects of contracting in the small farm sector were analyzed in many previous studies, labor market and employment effects are not yet well understood. This is an important research gap, especially against the background of continued population growth and structural transformation. Here, we investigate the effects of two types of contractual agreements between large international processing companies and smallholder farmers on agricultural labor use, household labor allocation, and hired labor demand in Ghana's palm oil sector. We use cross-sectional survey data and a willingness-to-pay approach to control for unobserved heterogeneity between farmers with and without contracts. We find that agricultural labor intensity is substantially reduced through the contracts, because contracting in Ghana is associated with the adoption of labor-saving procedures and technologies. Simple marketing contracts lead to reallocation of the saved household labor to off-farm employment, whereas resource-providing contracts lead to a stronger reallocation of labor within the farming enterprise. Household labor is more affected by labor savings than hired labor.
Keywords: 330; agricultural labor use; child labor; contract farming; gender; oil palm; rural employment